A graphene/hemin hybrid material as an efficient green catalyst for stereoselective olefination of aldehydes. Issue 121 (23rd November 2015) - Joshi, Chetan; Kumar, Pawan; Behera, Babita; Barras, Alexandre; Szunerits, Sabine; Boukherroub, Rabah; Jain, Suman L.
Abstract : A hemin/graphene composite was investigated for olefination of aldehydes using ethyl diazoacetate in the presence of triphenylphosphine. Abstract : A hemin/graphene composite, prepared by mixing an aqueous solution of graphene oxide (GO) with hemin and sonicating the suspension for 5 h at room temperature, was investigated for olefination of aldehydes using ethyl diazoacetate in the presence of triphenylphosphine. Efficient olefination of aromatic aldehydes with high ( E )-selectivity was obtained, revealing that rGO/hemin is a promising heterogeneous catalyst for the olefination reaction. The as-synthesized catalyst could easily be recovered from the reaction mixture and was subsequently used for several runs without any significantly loss in activity and selectivity.